1997
DOI: 10.1046/j.1365-2362.1997.2280786.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative autoaggression by phagocytes in human peritonitis

Abstract: In 60 abdominal exudates from patients with the diagnosis of either acute or persistent (chronic) peritonitis, indicators of phagocyte-derived oxidative systems (myeloperoxidase, chemiluminescence) and proteases (elastase) were measured. These exudates reveal a picture of maximal inflammatory activation. Both types of exudates (30 each) showed a significant influx of inflammatory cells, with the mean leucocyte count being 73,000 microL and 32,000 microL-1 respectively. Local myeloperoxidase concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…The ROS produced are intended to destroy invading organisms and damaged tissues. Despite these beneficial effects, the overwhelming oxidative stress can result in additional tissue destruction [31]. It has also been reported that low levels of ROS are involved in various metastatic processes, such as adhesion, invasion and proliferation [12][13][14][15][16]32].…”
Section: Discussionmentioning
confidence: 99%
“…The ROS produced are intended to destroy invading organisms and damaged tissues. Despite these beneficial effects, the overwhelming oxidative stress can result in additional tissue destruction [31]. It has also been reported that low levels of ROS are involved in various metastatic processes, such as adhesion, invasion and proliferation [12][13][14][15][16]32].…”
Section: Discussionmentioning
confidence: 99%
“…The proteinase inhibitors responsible for the control of NE activity are α 1 -proteinase inhibitor (α 1 -PI), α 2 -macroglobulin, and mucus proteinase inhibitor. In vivo, the inhibition of NE by mucus proteinase inhibitor and α 1 -PI may be affected by compounds present at the site where the inhibition reaction takes place, with oxidants released by polymorphonuclear neutrophils present at sites of inflammation reducing the capacity of NE inhibition by α 1 -antitrypsin (33) and α 1 -PI (34). On the other hand, when heparin is administered to some patients, it will bind NE and decrease its rate of inhibition by α 1 -PI (5).…”
Section: Glycosaminoglycan Participation In Extracellular Matrix Degrmentioning
confidence: 99%
“…Reactive oxygen species (ROS) have traditionally been viewed as a destructive force 1 2. However, there is growing evidence to demonstrate that ROS have Jekyll and Hyde characteristics which contribute significantly to tumour cell development 3–6.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the acute phase response associated with surgical trauma has been proposed as the main contributor to elevation of ROS levels postoperatively 1 2. However, there is an untold side to this story in the form of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (Nox) enzymes which are now known to be overexpressed in non-phagocytic cells such as cancer cells 20.…”
Section: Introductionmentioning
confidence: 99%